2022
DOI: 10.1101/2022.05.10.491101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transposable elements are associated with the variable response to influenza infection

Abstract: SUMMARYInfluenza A virus (IAV) infections are frequent every year and result in a range of disease severity. Given that transposable elements (TEs) contribute to the activation of innate immunity, we wanted to explore their potential role in this variability. Transcriptome profiling in monocyte-derived macrophages from 39 individuals following IAV infection revealed significant inter-individual variation in viral load post-infection. Using ATAC-seq we identified a set of TE families with either enhanced or red… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Notably, Chen et al. 37 found that SVA families are overrepresented in open chromatin in macrophages infected with influenza and are variable between individuals ( Figure S18 ). Consistent with this, the overwhelming majority of ATAC-seq peaks that lie on SVA polymorphisms were detected in the infected condition (92 of 108 peaks, 85.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Chen et al. 37 found that SVA families are overrepresented in open chromatin in macrophages infected with influenza and are variable between individuals ( Figure S18 ). Consistent with this, the overwhelming majority of ATAC-seq peaks that lie on SVA polymorphisms were detected in the infected condition (92 of 108 peaks, 85.2%).…”
Section: Resultsmentioning
confidence: 99%
“…A similar trend is observed with TE biomarkers like MER48, and MER54A, suggesting these TEs are accessible in uninfected monocytes but transcriptionally dormant. This leads us to propose that such TEs may be primed to a “poised” state that might correlate to monocyte function [50]. Notably, several of these TEs, previously identified as “poised”, featured prominently among the upregulated TEs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have characterized TE expression in response to infection with different viruses and found that infection-induced genome-wide TE expression often occurs in the vicinity of antiviral response genes (Chen et al ., 2023; Macchietto et al ., 2020). Thus, de-repression of TEs might have cis -acting consequences on regulating the expression of these antiviral response genes (Chuong et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, IAV is not the only type of pathogen described to upregulate various host retroelements during infection (Young et al , 2014). Recently published re-analyses of publicly available gene expression datasets showed that infection with a diverse range of viruses can trigger changes in TE expression (Chen et al , 2023; Macchietto et al , 2020), indicating that the insights on molecular mechanisms leading to IAV-induced TE expression and sensing could be broadly applicable to other viruses.…”
Section: Introductionmentioning
confidence: 99%